Peptide-coated polyurethane material reduces wound infection and inflammation. (1st July 2021) - Strömdahl, Ann-Charlotte; Ignatowicz, Lech; Petruk, Ganna; Butrym, Marta; Wasserstrom, Sebastian; Schmidtchen, Artur; Puthia, Manoj
Abstract: There is an urgent need for treatments that not only reduce bacterial infection that occurs during wounding but that also target the accompanying excessive inflammatory response. TCP-25, a thrombin-derived antibacterial peptide, scavenges toll-like receptor agonists such as endotoxins and lipoteichoic acid and prevents toll-like receptor-4 dimerization to reduce infection-related inflammation in vivo . Using a combination of biophysical, cellular, and microbiological assays followed by experimental studies in mouse and pig models, we show that TCP-25, when delivered from a polyurethane (PU) material, exerts anti-infective and anti-inflammatory effects in vitro and in vivo . Specifically, TCP-25 killed the common wound pathogens, Pseudomonas aeruginosa and Staphylococcus aureus, in both in vitro and in vivo assays. Furthermore, after its release from the PU material, the peptide retained its capacity to induce its helical conformation upon endotoxin interaction, yielding reduced activation of NF-κB in THP-1 reporter cells, and diminished accumulation of inflammatory cells and subsequent release of IL-6 and TNF-α in subcutaneous implant models in vivo . Moreover, in a porcine partial thickness wound infection model, TCP-25 treated infection with S. aureus, and reduced the concomitant inflammatory response. Taken together, these findings demonstrate a combined antibacterial and anti-inflammatory effect of TCP-25 delivered from PU in vitro, and in mouse and porcine in vivo models of localized infection-inflammation. Statement of significance: Local wound infections may result in systemic complications and can be difficult to treat due to increasing antimicrobial resistance. Surgical site infections and biomaterial-related infections present a major challenge for hospitals. In recent years, various antimicrobial coatings have been developed for infection prevention and current concepts focus on various matrices with added anti-infective components, including various antibiotics and antiseptics. We have developed a dual action wound dressing concept where the host defense peptide TCP-25, when delivered from a PU material, targets both bacterial infection and the accompanying inflammation. TCP-25 PU showed efficacy in in vitro and experimental wound models in mouse and minipigs. Graphical abstract: Image, graphical abstract